THE RELATIONSHIP BETWEEN SANITATION PERCEPTION AND THE INCIDENCE OF RESPIRATORY TRACT INFECTION (RTI) IN CORRECTIONAL INSTITUTION: Hubungan Persepsi Sanitasi dengan Kejadian Respiratory Tract Infection (RTI) di Lembaga Pemasyarakatan - Satria, Hardiat Dani; Budi Musthofa, Syamsulhuda; Sakundoro Adi, Mateus (Universitas Airlangga, 2025)
Background: The incidence of respiratory tract infection (RTI) in Class IIA Correctional Institution (Lapas) Kendal is notably high. RTI consistently ranks as the most common illness occurring each month, accounting for over 50% of all diseases within the facility. Previous research has indicated that one of the contributing factors to RTI is poor sanitation conditions within the correctional institution. Purpose: This study aims to analyze the relationship between sanitation perceptions and the incidence of RTI in Class IIA Correctional Institution Kendal. Methods: This quantitative study uses a cross-sectional research design with a sample of 294 inmates from the Class IIA Correctional Institution Kendal. The sample was selected using total sampling, involving all inmates in the facility. A Chi-Square test was applied for bivariate analysis. Results: The variable of sanitation perception showed a significant relationship with the incidence of RTI in Class IIA Correctional Institution Kendal. The p-value for the Pearson Chi-Square test was 0.00. Sanitation perception factors included building indicators (p=0.02), room indicators (p=0.54), drinking water indicators (p=0.06), and waste indicators (p=0.00). Conclusion: Sanitation perception factors, such as building indicators and waste indicators, are associated with the incidence of RTI in Class IIA Correctional Institution Kendal. Meanwhile, room indicators and drinking water indicators were not related to the incidence of RTI. To achieve the Sustainable Development Goals (SDGs, it is necessary to implement the Water, Sanitation, and Hygiene (WASH) concept within the correctional institution to minimize the transmission of RTI.